Raw deal: how the "Uber economy" and runaway capitalism are screwing American workers - Hill, Steven (New York, 2015)
"Currently a senior fellow with New America, Hill is a long-time journalist and commentator. His work has been featured in The Washington Post, The Guardian, the BBC, C-Span, and many other outlets. In his fifth book, the author of Europe’s Promise takes a hard look at new businesses like Uber, Airbnb, and TaskRabbit—and finds them wanting. Arguing against the sharing economy as a model, Hill shows how this libertarian economy is unfair to workers, who are less likely to be full-time employees and more likely to work as contractors—meaning they hire themselves out for small jobs at low compensation. A fairer deal for America’s labor force, which also faces displacement from robots and automation, Hill suggests, is an economic model focused on the individual, not the workplace."